2020
DOI: 10.3390/su12145638
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Urban Flood Resilience in Barcelona for Current and Future Scenarios. The RESCCUE Project

Abstract: The results of recent climate projections for the city of Barcelona show a relevant increment of the maximum rainfall intensities for the period 2071–2100. Considering the city as a system of systems, urban resilience is strictly linked to the proper functioning of urban services and the knowledge of the cascading effects that may occur in the case of the failure of one or more critical infrastructures of a particular strategic sector. In this context, the aim of this paper is to assess urban resilience throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In this framework, some potential hazards for strategic urban services produced by a set of selected climate change pressures have been identified and selected depending on their significance and the interest in each research site (Table 3). The effects of these climate drivers on strategic urban services have been analyzed through detailed models and tools developed and calibrated within the project [11][12][13][14][15].…”
Section: Hazard Assessment Summary For the Three Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, some potential hazards for strategic urban services produced by a set of selected climate change pressures have been identified and selected depending on their significance and the interest in each research site (Table 3). The effects of these climate drivers on strategic urban services have been analyzed through detailed models and tools developed and calibrated within the project [11][12][13][14][15].…”
Section: Hazard Assessment Summary For the Three Citiesmentioning
confidence: 99%
“…In terms of hazard analysis, for the case of Barcelona, the simulation results showed that climate change could significantly exacerbate flood hazard in the sectors of urban drainage, electricity, traffic and waste collection, while its effects on water quality (bathing water and river) seemed to be negligible [11,13]. Sea level rise analysis performed by GIS tools indicated moderate loss of beaches for the horizon of 2050 and 2100, although its effects should not affect critical infrastructures located in the vicinity of the coast.…”
Section: Hazard Assessment Summary For the Three Citiesmentioning
confidence: 99%
“…For example, Ma [6] defined vulnerability as an adaptive function of the load capacity of stations and extreme weather conditions and analyzed the impact of extreme weather conditions on public transport networks. Others have viewed vulnerability to be related to the occurrence possibility of sudden events and have considered vulnerability as the product of the probability of URTN operation failure [7,8]. Sun [9] investigated the vulnerability of URTN operations using the relative failure probability.…”
Section: Introductionmentioning
confidence: 99%
“…Adapting modern cities to face future changes, including climate changes, requires modification of the main urban services design requirements, such as improved drainage systems to cope with extreme rainfall intensity producing flood events [1][2][3][4][5]. As rainfall events become more extreme, each city requires a personalized solution to cope with the problem of undersized sewer networks and poor surface drainage systems [6].…”
Section: Introductionmentioning
confidence: 99%